How to attract talents? Field-experimental evidence on emphasizing flexibility and career opportunities in job advertisements - Larissa Fuchs; Matthias Heinz; Pia Pinger; Max Thon (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Job advertisements are a key instrument for companies to attract talent. We conduct a field experiment in which we randomize the content of job advertisements for STEM jobs in one of the largest European technology firms. Specifically, we study how highlighting job flexibility and career advancement in job advertisements causally affects the firm's pool of applicants. We find large treatment effects of entry-, but not for senior-level positions in the firm: highlighting job flexibility increases the total number of female and male applicants, while emphasizing career advancement only raises applications by men. Both effects are entirely driven by applicants residing outside of the federal state in which the firm is located. In a survey experiment among STEM students, we find that the content of job advertisements shapes young professionals' beliefs about the work environment at the firm. Most importantly, we find that students expect better career benefits, but lower work-life balance when career advancement are highlighted. Our study highlights how job advertisements affect the total number of applications as well as applicants' quality, diversity, region of residence and beliefs.
Keywords: M51; M52; D22; 330; beliefs; hiring; field experiments; survey experiment; job advertisements; gender